Rhabdomyolysis after the free fibular flap operation for mandibular reconstruction: a case report - Choi, Won-Hyuk (Maxillofac Plast Reconstr Surg, 2018)
BACKGROUND: Free fibular flap is one of the most useful methods in the hard tissue reconstruction of the maxilla-mandible. Free fibular flap presents some advantages in which the reconstruction of both soft and hard tissues can be done at the same time. It also provides a safe and successful bone graft for the reconstruction, along with a low rate of complications. Despite these advantages and the rarity of a postoperative complication, particularly in oral and maxillofacial surgery procedures, a prolonged operation might exhibit some complications related with rhabdomyolysis. We experienced the rare event of rhabdomyolysis after oral cancer surgery. CASE PRESENTATION: In this article, we report the case of a patient who developed rhabdomyolysis after undergoing free fibular flap surgery. CONCLUSIONS: Despite the advantages of the free fibular flap operation, clinicians must be aware of the risk of complications because there are multiple factors that could result in rhabdomyolysis, such as duration of operation, position of the subject, and pre-existing conditions of diabetes and hypertension. Once the diagnosis of rhabdomyolysis is confirmed, a prompt treatment plan should be made and applied as soon as possible. This will increase the chance of a full recovery for the patient who is exhibiting symptoms of rhabdomyolysis.